Plasma-electrolytes in natives to hypoxia after marathon races at different altitudes - Schmidt, W.; Rojas, J.; Boning, D.; Bernal, H.; Garcia, S.; Garcia, O. (Medicine & Science in Sports & Exercise, 1999)
Purpose: It is well known that altitude natives differ from sea level natives in aspects of fluid and electrolyte homeostasis. Conclusion: Under tropical conditions, we found a severe state of dehydration characterized by an extended ANP-response, which was not prevented by water intake during the race. Under hypoxic conditions, however, we found that hyponatremia had developed. This can be partly explained by pure water intake and metabolically produced water, and also, possibly, by a special hypoxia-induced effect.